2020
DOI: 10.1111/sode.12478
|View full text |Cite
|
Sign up to set email alerts
|

How socialization goals and peer social climate predict young children's concern for others: Evidence for a development shift between 2 and 4 years of age

Abstract: Children's concern for others is shaped through socialization, but current theories make different predictions as to how and when in development this socializing occurs. Here we found that mothers' prosocial socialization goals (SGs) predicted concern for others in 2‐year‐old (n = 804) and 4‐year‐old (n = 714) children. In contrast, preschool teachers' SGs predicted concern for others only for 4‐year‐old children. In addition, a positive social climate among classroom peers predicted 4‐year‐olds' prosociality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 73 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…New data are provided confirming that daycare attendance does not appear to have an impact on the enactment of prosocial behaviors when considering the total amount of such behaviors, not only in the immediate ( Bleiker et al, 2019 ), but also in later periods ( Pingault et al, 2015 ; Schmerse and Hepach, 2021 ). However, at the same time, this early socialization experience appears to negatively influence, specifically, the production of prosocial acts following a request from a peer.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…New data are provided confirming that daycare attendance does not appear to have an impact on the enactment of prosocial behaviors when considering the total amount of such behaviors, not only in the immediate ( Bleiker et al, 2019 ), but also in later periods ( Pingault et al, 2015 ; Schmerse and Hepach, 2021 ). However, at the same time, this early socialization experience appears to negatively influence, specifically, the production of prosocial acts following a request from a peer.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, the daycare experience requires children to create new relationships outside the family very early on, and this means to engage in interactions with peers, to adapt to teachers’ expectations and demands, and to test and modify their social-emotional abilities by experience ( Hyson and Taylor, 2011 ; Grazzani et al, 2016 ). As some studies have shown, while attending daycare children are frequently exposed to prosocial behaviors and, consequently, they are prone to enact such behaviors themselves for two main reasons: one refers to social imitation processing, the other to the evidence that through the care that the young children receive, they learn to care for others ( Quigley and Hall, 2016 ; McCormick, 2018 ; Bleiker et al, 2019 ; Schmerse and Hepach, 2021 ). Furthermore, the study of Over and Carpenter (2009) evidenced that the mere condition of familiarizing children with photographs in which group situations are represented, and thus clearly affiliative and social, leads them to enact more helping behaviors than children who have been exposed to non-affiliative pictures, in which isolated individuals are represented.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations